Imaginary geography. On example of «card» in Gilles Deleuze’s work (Journal of Philosophy Culture and Political Science, 2018)
The article explains the specificity of philosophical example in so-called post-modern philosophy. The article analyses an example of «card» in the works of the French philosopher Gilles Deleuze. The author of the article analyses categories as «nomadology», «card / calque», «system», «rhizome», as well as the context in which these categories (notions) are used in the books of the philosopher.Key words: sistema, thought karta / kalka, nomadichesky / sedentarny (nomadic / sedentary) rizoma / tree.